Health Education Uses Media Images And Videos To Increase Sadari Motivation at Young Women - Tantiana Isnaningsih (Jurnal Teknologi Pembelajaran, 2021)
Breast cancer ranked first in hospitalization patients in Indonesia (16.85%), followed by cervical cancer (11.87%). Cancer itself can actually be prevented, treated and cured if it is known early signs and symptoms of cancer. Early screening of cancer symptoms can be done on its own so that it can be done at any time and at no cost. The purpose of this study is to find out the Influence and Benefits of Health Education through the medium of images and videos to increase the motivation of conducting their own breast screening (be aware) of cancer prevention in Young Women at 1 Senior High School of Bantul Yogyakarta. The research used a research design using the one group pretest-posttest design method. The population in this study is grade X students at 1 Senior High School of Bantul Yogyakarta. Sampling technique using purposive sampling as many as 30. Analyze data using wilcoxon test. The motivation level after getting health education most respondents for the good category are 30 people (100%). The test results showed a value of p - value= 0.000 (p < 0.05) meaning that there is an influence of health education through the media of images and videos on the motivation to perform breast examinations themselves (be aware) in young women at 1 Senior High School of Bantul Yogyakarta